GAMBARAN PENGETAHUAN GIZI SEIMBANG DAN ASUPAN ZAT GIZI SISWA-SISWI DI SMP NEGERI 2 AIR PUTIH - Lusyana Gloria Doloksaribu; Novi Arianti Br. Damanik (POLTEKKES KEMENKES MEDAN, 2021)
Background Knowledge of a teenager is mainly influenced by education. Low education and lack of knowledge of nutrition can lead to irregular behavior and eating habits so that it becomes the cause of nutritional problems. Therefore, adolescents need adequate food both in terms of quality and quantity. The better the nutritional knowledge of teenagers, the more varied or varied the food consumed, the more fulfilled the nutritional adequacy. The purpose of this research is to know the description of nutritional knowledge and nutrient intake of students of SMP Negeri 2 Air Putih. The type of research used is a descriptive survey with a cross sectional design. The number of samples in this study were 78 teenagers who were taken by total sampling, the data collection methods were interviews using questionnaires and 24-hour food recall. The results showed that 39.7% of knowledge was in the good category with 17.9% carbohydrate intake in the good category, 17.94% protein intake in the good category, 15.38% fat intake in the good category, 32.1% calcium intake in the medium category and 39.7% iron intake in the less category. Conclusions Knowledge of balanced nutrition of students is still low (39.7%) as well as the average intake of nutrients in the good category is only 24.6% of the recommended nutritional adequacy.